The Effect of Financial Distress and Growth Opportunities on Accounting Conservatism with Litigation Risk as Moderated Variables in Manufacturing Companies Listed on BEI - Warsani Purnama Sari (Budapest International Research and Critics University, 2020)
This study aims to examine and analyze the effect of financial distress and growth opportunities on accounting conservatism with litigation risk as a moderating variable. The population in this study were 147 manufacturing companies listed on the Indonesia Stock Exchange for the period 2015-2017, with a purposive sampling technique so that 102 samples were obtained. The method of data analysis uses multiple linear regression analysis and interaction testing with the help of the Eviews application program. The results showed that financial distress and growth opportunities partially had a positive and significant effect on accounting conservatism. Litigation risk as a moderating variable strengthens the effect of litigation risk on accounting conservatism, and litigation risk weakens the effect of growth opportunities on accounting conservatism on Manufacturing companies listed on the Indonesia Stock Exchange for the period 2015-2017.